1976
DOI: 10.1002/bip.1976.360151006
|View full text |Cite
|
Sign up to set email alerts
|

Relative stability of the α‐helix of deuterated poly(γ‐benzyl‐L‐glutamate)

Abstract: SynopsisThe coil-to-helix transition temperatures of hydrogen bearing and deuterated poly(7-benzyl-L-glutamate) in 1,3-dichlorotetrafluoroacetone/H~O and / D 2 0 mixtures, respectively, have been determined. Together with previously obtained data for the conformational transition of this polypeptide in normal and deuterated dichloroacetic acid, these results have been used in an analysis of the effect of deuterium substitution on the intrinsic stability of the tu-helical form of poly(y-benzyl-L-glutamate). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In addition, they examined the effects of D 2 O on actin polymerization in vitro and demonstrated that D 2 O accelerates purified globular actin polymerization immediately upon exposure to D 2 O, whereas the total amount of polymerized actin later during treatment with D 2 O is the same as that in H 2 O. Therefore, one possible mechanism underlying D 2 O-induced actin filament redistribution may involve the hydrogen to deuterium exchange in globular proteins (Hermans and Scheraga, 1959;Scheraga, 1960), which results in more stable protein structures (Sing and Wood, 1969;Karasz and Gajnos, 1976), and thus is caused by a typical isotope exchange effect.…”
Section: Cellular Responses Under D 2 O Exposurementioning
confidence: 99%
“…In addition, they examined the effects of D 2 O on actin polymerization in vitro and demonstrated that D 2 O accelerates purified globular actin polymerization immediately upon exposure to D 2 O, whereas the total amount of polymerized actin later during treatment with D 2 O is the same as that in H 2 O. Therefore, one possible mechanism underlying D 2 O-induced actin filament redistribution may involve the hydrogen to deuterium exchange in globular proteins (Hermans and Scheraga, 1959;Scheraga, 1960), which results in more stable protein structures (Sing and Wood, 1969;Karasz and Gajnos, 1976), and thus is caused by a typical isotope exchange effect.…”
Section: Cellular Responses Under D 2 O Exposurementioning
confidence: 99%
“…They concluded that alteration of stress fibres in cultured cells may be caused by a direct effect of D 2 O on cellular microfilament dynamics (Omori et al, 1997). One possible mechanism underling D 2 O-induced actin filament redistribution may involve H to D exchange in globular protein (Hermans & Scheraga, 1959;Scheraga, 1960), which results in a more stable protein structure (Karasz & Gajnos, 1976;Sing & Wood, 1976).…”
Section: Effect Of D 2 O On the Actin Structurementioning
confidence: 99%